An Evaluation of Early Childhood Educators’ Knowledge of Their Professional Code of Conduct - Rachael Ojima Agarry (Indonesian Journal of Multidiciplinary Research, 2022)
Teachers of young children have precise responsibilities towards children and their families, colleagues at workplaces as well as the community. This study assessed how knowledgeable early childhood educators are in terms of their professional code of conduct. Four research questions were answered and three hypotheses were tested at a 0.05 level of significance. Two hundred (200) respondents were randomly sampled to participate in the study. A validated instrument tagged “ECE Professional Code Test” (ECEPCT) with a reliability coefficient of 0.73 was used to collect data for the study. Findings revealed that early childhood educators’ knowledge of their responsibilities towards the children, their families, and the community was low while the level of their knowledge of their responsibilities towards their colleagues was high. In addition, it was revealed that gender, academic qualification, and school type have no significant influence on early childhood educators’ knowledge of their professional code of conduct. Because of these outcomes, it was recommended that issues on professional ethics and code of conduct should be incorporated and emphasized during pre-service training of early childhood educators as well as during seminars and re-training of in-service caregivers/teachers. In addition, a handbook on professional ethics and code of conduct for early childhood educators should be made available and accessible to all caregivers and teachers of young children.